1977
DOI: 10.1073/pnas.74.5.2054
|View full text |Cite
|
Sign up to set email alerts
|

Triiodothyronine stimulates specifically growth hormone mRNA in rat pituitary tumor cells.

Abstract: In a cell-free protein-synthesizing system from a rabbit reticulocyte lysate, total RNA extracted from cultured rat pituitary tumor (GH3) cells directed, in a dose-related manner, the synthesis of proteins that were precipitated by antisera specific to rat growth hormone (somatotropin) and rat prolactin. A marked decrease in growth hormone secretion and growth hormone mRNA activity was observed when cells were grown in a medium deficient in thyroid hormone. Addition of triiodothyronine in physiologic amounts b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
1

Year Published

1979
1979
1986
1986

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(46 citation statements)
references
References 24 publications
1
44
1
Order By: Relevance
“…The visible band was collected, resuspended in PBS, and pelleted at 20000 r.p.m, for 1 h. The virion RNA (vRNA) was extracted repeatedly with phenol--chloroform (1 : 1), precipitated from the final aqueous phase with 2 M-LiC1 for 16 h at 4 °C and dissolved in distilled water. The amount of RNA was calculated assuming that 1 A260 unit is 40 ~tg/ml (Seo et al, 1977). 125 I-labelled vRNA was prepared by the thallium chloride procedure of Tereba & McCarthy (1973).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The visible band was collected, resuspended in PBS, and pelleted at 20000 r.p.m, for 1 h. The virion RNA (vRNA) was extracted repeatedly with phenol--chloroform (1 : 1), precipitated from the final aqueous phase with 2 M-LiC1 for 16 h at 4 °C and dissolved in distilled water. The amount of RNA was calculated assuming that 1 A260 unit is 40 ~tg/ml (Seo et al, 1977). 125 I-labelled vRNA was prepared by the thallium chloride procedure of Tereba & McCarthy (1973).…”
Section: Methodsmentioning
confidence: 99%
“…Extraction of RNA from uninfected cells (1 x 10 s cells) was carried out according to the method of Seo et al (1977). The extracted RNA preparations were serially diluted in 30 ~tl of distilled water, mixed with 20 ~tl of 0-1 M-Tris HC1 pH 7.4, containing 0.75 M-NaC1, 5 mM-EDTA, 0.05 ~ SDS, and 125I-labelled vRNA and held at 68 °C for 96 h. Each mixture was then split into two parts, one being treated with S 1 nuclease at 40 °C for 1 h and the other left at 40 °C.…”
Section: Methodsmentioning
confidence: 99%
“…A number of recent studies have shown that glucocorticoid (16,17,18) and thyroid (17,18,19) hormones increase the amount of pregrowth hormone mRNA in these cultured cells, while thyrotropin-releasing hormone increases the amount of preprolactin mRNA (9,20). A long-range goal of our work is to establish whether glucocorticoid and thyroid hormones bring about an increase of pregrowth hormone mRNA (pGH mRNA) due to increased transcription or some post-transcriptional event.…”
Section: Introductionmentioning
confidence: 99%
“…phenol-chloroform (1 : 1), precipitated from the final aqueous phase with 2 M-LiCI for 16 h at 4 °C and dissolved in distilled water. The amount of RNA was calculated assuming that one A_,60 unit is 40 ~tg/ml (Seo et al, 1977).…”
mentioning
confidence: 99%
“…Mock-infected or influenza B virus-infected cells were harvested 3-5 h after infection. The extraction of cellular RNA was carried out according to the method of Seo et al (1977).…”
mentioning
confidence: 99%